CATIONIC NANOSTRUCTURED LIPID CARRIERS: OPTIMIZATION OF ZETA POTENTIAL AND EVALUATION - BAIG, MIRZA SALMAN; SIDDIQUI, AQUIL-UR-RAHIM (International Journal of Applied Pharmaceutics, 2020)
Objective: To fabricate, optimize and evaluate, Lipid-based cationic nanoparticulate dispersed system to improve the bio-adhesion property for ophthalmic use. Methods: Lipid-based cationic nanoparticulate dispersed system was fabricated by melt emulsification ultrasonication method and Box-Behnken design was utilized for optimization of formulation through the Design-Expert® program. The concentration of stabilizer, liquid lipid and Cetyltrimethylammonium Bromide (CTAB) was selected as variables (factors) while particle size, zeta potential and polydispersity index (PDI) were selected as a response for optimization purpose. Characterization of particle properties was performed using Transmission Electron Microscopy (TEM), Photon correlation spectroscopy (PCS). Fourier-transform infrared spectroscopy (FT-IR) was performed to study chemical interaction among ingredients. Rhodamine B entrapped CNLC formulation was used to study the interaction of NLC and CNLC on a three-dimensional and two-dimensional ocular tissue model for cell uptake and penetration properties. Results: Cationic nanostructured lipid carrier system was successfully fabricated by melt emulsification ultrasonication method. Characterization of nanoparticulate system using PCS revealed particle size in the range of 113.1 to 274.2 nm, PDI in a range of 0.147 to 0.280, while zeta potential in the range of 7.2 to 49.8 mV. The validation of statistical design suggested that it was suitable for navigation of design space. TEM imaging confirmed the results of PCS characterization. FT-IR study suggested a minimal chemical interaction among ingredients in CNLC. Confocal laser microscopic imaging for the interaction of NLC and CNLC on a three-dimensional and two-dimensional ocular tissue model revealed good penetration and bio-adhesion properties. Conclusion: The fabricated Cationic nanostructured lipid carrier system was found to be the potential ophthalmic novel drug delivery system with good bio-adhesion and penetration properties.